Antiplatelet therapy: present status and its future directions - Ahluwalia, Kaza; Bhanwra, Sangeeta (International Journal of Basic & Clinical Pharmacology, 2017)
Anti-platelets drugs play an important role in the prevention or treatment of cardiovascular diseases e.g. coronary artery disease, stroke, etc., which cause high mortality and morbidity in the present day world. These drugs either inhibit the platelet activation, aggregation or other signaling pathways, thereby inhibiting the clot formation. The anti-platelet drugs currently used are aspirin, ADP receptor inhibitors (ticlopidine and clopidogrel)and glycoprotein (GP)IIb/IIIa inhibitors (abciximab, tirofiban and eptifibatide). Aspirin was and still continues to be the main anti-platelet therapy. A combination regimen of aspirin and clopidogrel is commonly used for the prevention of platelet activation, thrombosis and stroke. However, many of the current anti-platelet drugs face limitations due to narrow therapeutic window and limited efficacy. The four possible targets for novel anti-platelet action are: Inhibition of agonist generation, receptor inhibition, G protein inhibition and inhibition of enzymatic cascades. Newer P2Y12 antagonists e.g. prasugrel, ticagrelor, cangrelor, etc., have better efficacy and low bleeding risk. The thrombin receptor (PAR1 and 4) inhibitors are said to decrease the hemorrhagic complications. Drugs which inhibit TXA2 Synthase or TXA2 receptor are also promising in their anti-platelet action. Another novel group is of collagen receptor antagonists such as GPVI antagonists, GPIb receptor antagonists, etc. The other targets being explored are von Willebrand Factor antagonists, platelet Gq antagonists, etc. However, there still lies a bundle of unresolved issues regarding the efficacy and safety, optimal dosage, administration requirements, combination therapy, clinical evaluation, cost-effectiveness, and the resistance phenomena of these drugs.